Placement technique impacts gastrostomy tube-related complications amongst head and neck cancer patients. (July 2022) - Forner, David; Mok, Florence; Verma, Neil; Karam, Irene; Goldstein, David; Higgins, Kevin; Enepekides, Danny; Nadler, Ashlie; Pugash, Robyn; Husain, Zain; Chan, Kelvin; Smoragiewicz, Martin; et al.
Graphical abstract: Highlights: Tube-related complications occur in one third of patients with percutaneous gastrostomy tube insertion. Complications are associated with the type of technique used to insert gastrostomy tubes, with the "push" technique associated with greater complications. The rate of stomal metastasis is low. Abstract: Objectives: Percutaneous endoscopic gastrostomy (PEG) placement is essential for the provision of enteral nutrition in select head and neck cancer (HNC) patients. Minimally invasive tube placement is facilitated through one of two techniques, push or pull, but there have been conflicting results regarding safety profiles of these procedures. The objectives of this study were to determine the association of PEG insertion technique with gastrostomy tube complications, including stomal metastases. Methods: A multi-institutional retrospective cohort study of patients with HNC undergoing PEG insertion by either the pull (gastroscope assisted) or push (fluoroscopy assisted) technique was performed. Tube-related complications included infection, dislodgement, deterioration, leak, and other. Adjusted analysis was performed via a multivariable logistic regression model. Results: 1, 575 patients were included across three institutions. Tube-related complications occurred in 36% of patients, the most common being peristomal leak (13%) and infection (16%). The push technique (OR 2.66, 95% CI: 1.42–4.97), and the presence of T4 disease (OR 4.62, 95% CI: 1.58–13.51), were associated with a greater risk of developing any tube-related complication. Infection rates were similar between pull and push cohorts. All detected stoma metastases occurred with the pull technique, with an overall prevalence of 0.32% amongst the cohort. Conclusions: The push technique is associated with a greater risk of developing any tube-related complication, but the rate of stomal metastases may be higher with the pull technique. There is potential for quality improvement measures to improve tube-related complications associated with either technique.